YouTube and the single-rod contraceptive implant: a content analysis. Issue 3 (20th January 2017) - Paul, Jennifer; Boraas, Christy M; Duvet, Mildred; Chang, Judy C
Abstract : Background: Since the internet has become an important source of contraceptive information with YouTube.com as the second most visited site, we analysed contraceptive implant YouTube videos for content and clinical accuracy. Methods: Using the terms 'contraceptive implant', 'Nexplanon' and 'Implanon', the top 20 results on YouTube by relevance and view count were identified. After excluding duplicates, single-rod implant videos in English were included. Videos were classified as providing a professional or patient perspective. Views, duration and comments were noted. Videos were rated for reliability, global quality scale and whether they were positive or negative about the implant. Inter-rater agreement was measured. Results: A total of 120 videos were retrieved; 52 were eligible for review. Less than 23% were professional videos; the majority reported patient experience (46% testimonials, 27% real-time procedure videos, 4% other). Patient videos had been posted a significantly longer duration of time than professional videos (364 vs 188 days, p =0.02), were less reliable ( p ≤0.0001) and were of lower global quality ( p <0.0001). Some 61% of implant testimonial videos were rated as 'positive experiences' and inter-rater agreement was very good (κ=0.81). All testimonials mentioned side effects, commonly irregular bleeding and discomfort with insertion. A minority (26%) reported misinformation. Conclusions: This study found that most of the information on YouTube pertaining to contraceptive implants is accurate, is presented from the patient's perspective, and promotes the method's use.